2010
DOI: 10.1128/aem.02765-09
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Permease (ActP) Is Responsible for Tellurite (TeO 3 2− ) Uptake and Resistance in Cells of the Facultative Phototroph Rhodobacter capsulatus

Abstract: The highly toxic oxyanion tellurite has to enter the cytoplasm of microbial cells in order to fully express its toxicity. Here we show that in the phototroph Rhodobacter capsulatus, tellurite exploits acetate permease (ActP) to get into the cytoplasm and that the levels of resistance and uptake are linked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…Despite the important role of this uptake activity, very few studies have addressed this issue. In R. capsulatus it has been shown that a mutant impaired in tellurite uptake became highly resistant to the oxyanion and the uptake defect was restored by the acetate permease actP2 gene [17], supporting an earlier observation indicating that acetate inhibits tellurite uptake in R. capsulatus cells, as both anions compete for the same permease [18]. This evidence led to the proposal that in R. capsulatus tellurite enters the cell mainly through the acetate transport system (RcActP2) [17,19].…”
Section: -mentioning
confidence: 61%
See 2 more Smart Citations
“…Despite the important role of this uptake activity, very few studies have addressed this issue. In R. capsulatus it has been shown that a mutant impaired in tellurite uptake became highly resistant to the oxyanion and the uptake defect was restored by the acetate permease actP2 gene [17], supporting an earlier observation indicating that acetate inhibits tellurite uptake in R. capsulatus cells, as both anions compete for the same permease [18]. This evidence led to the proposal that in R. capsulatus tellurite enters the cell mainly through the acetate transport system (RcActP2) [17,19].…”
Section: -mentioning
confidence: 61%
“…capsulatus is the acetate carrier ActP2, encoded by the actP2 gene [17], while the actP1 gene product , apparently, appears to have a minor role in the uptake of this oxyanion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, photosynthetic-anaerobically grown cells show a very high minimal inhibitory concentration (MIC) for tellurite ([800 lM) while dark-aerobically grown cells show an extremely low MIC for tellurite (%8 lM) (Borghese et al 2004). It was shown that intermediates of the TCA cycle such as malate, succinate or fumarate, when used as growth carbon sources, make the cells very sensitive to tellurite; conversely, other metabolites such as pyruvate or acetate drastically increase the MIC for the oxyanion by competing with tellurite for the same entry port (Borghese et al 2008), which has been identified as an acetate permease (ActP) (Borghese and Zannoni 2010).…”
mentioning
confidence: 99%
“…To investigate on the expression of actP gene in cells grown on different carbon sources, the reporter gene lacZ was fused to the previously cloned acetate permease gene (actP) (Borghese and Zannoni 2010), giving plasmid pRB71 that carries lacZ fused to the first portion of the operon that includes acs (acetylCoA synthetase) and actP (see Supplementary Material). As shown in Fig.…”
mentioning
confidence: 99%